Comparison of municipal solid waste management systems using the economic input-output life cycle assessment method - ORAK, NUR HANİFE (My University, 2022)
Solid waste management is not only an environmental problem but also causes universal economic loss. Within the scope of this study, existing field data for packaging waste management systems in Avcilar Municipality of Istanbul, Turkey, is used to compare the environmental impacts of the current collection method with the alternative collection scenarios. The Economic Input-Output Life Cycle Assessment (EIO-LCA) method is used for the analysis. The field data obtained by the licensed packaging waste collection company of Avc?lar Municipality through field observations. For this stage, a recording system was developed in the sorting facility and the expenditures of 18 different items such as waste amounts, fuel costs, and worker expenses. NAICS codes and expenditure items in the packaging waste sectors were matched. In this study, Scenario 1 (S1), Scenario 2 (S2), and Scenario 3 (S3) were defined as 0% separation rate (mix waste), current separation rate (1.6%), and 50% separation rate. Results show that CH4 is the main contributor to the total GHG emission for S2, while CO2 becomes an equally important emission for S3. The main reason of high CH4 emission in S2 can be the increased amount of mixed waste with organic waste content. The increase of CO2 in S2 compared to S1 can be related to several factors such as more vehicle use and related fuel consumption in S2. There is no significant change for N2O and other emissions between different collection scenarios. Among the three scenarios, S3 has the lowest GHG emission value: 950 t CO2-eq less than S2 and 454 t CO2-eq less than S1. The results show that alternative package waste management systems and better practices have a high potential to reduce GHG emissions in Istanbul and other cities of Turkey.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Engineering, Computing & Technology (ENG)